The role of APOE4 in Alzheimer's disease: strategies for future therapeutic interventions. Issue 2 (18th April 2019) - Hunsberger, Holly C.; Pinky, Priyanka D.; Smith, Warren; Suppiramaniam, Vishnu; Reed, Miranda N.
Abstract: Alzheimer's disease (AD) is the leading cause of dementia affecting almost 50 million people worldwide. The ε4 allele of Apolipoprotein E (APOE) is the strongest known genetic risk factor for late-onset AD cases, with homozygous APOE4 carriers being approximately 15-times more likely to develop the disease. With 25% of the population being APOE4 carriers, understanding the role of this allele in AD pathogenesis and pathophysiology is crucial. Though the exact mechanism by which ε4 allele increases the risk for AD is unknown, the processes mediated by APOE, including cholesterol transport, synapse formation, modulation of neurite outgrowth, synaptic plasticity, destabilization of microtubules, and β-amyloid clearance, suggest potential therapeutic targets. This review will summarize the impact of APOE on neurons and neuronal signaling, the interactions between APOE and AD pathology, and the association with memory decline. We will then describe current treatments targeting APOE4, complications associated with the current therapies, and suggestions for future areas of research and treatment.